Radar : International Art Exhibition in the City of Kotka/Finland. - Weber, Norbert (Kotka : City Kotka, 1990)
Ahtila, Eija-Liisa ; Art Blja ; Breivik, Bard ; Dluzniewski, Andrzej ; Filonik, Miroslaw ; Höller, Carsten ; Kivi, Jussi ; Lapin, Leonhard ; Mattheuer, Wolfgang ; Navakas, Mindaugas ; Norgaard, Bjorn ; Orfali, Ingrid ; Pétersons, Ojars ; Rheinsberg, Raffael ; Tapper, Kain ; Westerlund, Karin
2 ex. : 1 catalogus : 80 p. : ill., 1 catalogus: Documentation / Dokumentation / Dokumentaatio, 53 p. : ill.
Radar : International Art Exhibition in the City of Kotka/Finland, 28.6. - 2.9.1990
boek